Minding the source: the impact of mindfulness on source monitoring - Alberts, Hugo J. E. M. (Legal and criminological psychology, 2017)
Purpose. This study addressed the impact of mindfulness on source monitoring. Methods. Participants engaged in a brief mindfulness meditation or received no intervention. Next, all participants watched a video of a crime and were then exposed to misinformation regarding this video. Using a source monitoring test, participants’ memory performance was measured. Results. Participants who performed the mindfulness meditation showed better source monitoring compared to controls. Mindfulness practice was not found to enhance memory performance. Conclusions. Mindfulness practice may entail an effective way to circumvent memory distortions due to incorrect source monitoring.